Involvement of energetic metabolism in the effects of ischemic postconditioning on the ischemic-reperfused heart of fed and fasted rats - Marina Prendes, María Gabriela (2011)
The effects of ischemic-postconditioning (IPOC) on functional recovery and cell viability of ischemic-reperfused hearts from fed and fasted rats were studied in relation to triacylglycerol and glycogen mobilization, ATP content, glucose-6-phosphate dehydrogenase activity and reduced/oxidized glutathione (GSH/GSSG). Oxidative damage was estimated by measuring thiobarbituric acid reactive substances (TBARS). IPOC improved contractile recovery and cell viability in the fed but attenuated them in the fasted hearts. In both groups ischemia lowered glycogen. IPOC further reduced it. Triacylglycerol remained unchanged during ischemia-reperfusion in both groups, but triacylglycerol mobilization was activated by IPOC in the fasted group. ATP was increased by IPOC in the fed hearts, but lowered in the fasted ones, which appeared to be associated with the rates of ATP synthesis in isolated mitochondria. In the fed hearts IPOC raised glucose-6-phosphate dehydrogenase activity and GSH/GSSG, and lowered TBARS. These results suggest that IPOC effects are associated with changes in the ATP supply, mobilization of energy sources and glutathione antioxidant ratio.